Communicating with the Spirits - Pócs, Éva; Klaniczay, Gábor (Budapest ; New York : Central European University Press, 2005)
Focuses on the problem of communication with the other world: the phenomenon of spirit possession and its changing historical interpretations, the imaginary schemes elaborated for giving accounts of the journeys to the other world and for communicating with the dead, and finally the historical archetypes of this kind of religious manifestation -- trance prophecy, divination, and shamanism.
TABLE OF CONTENTS; LIST OF ILLUSTRATIONS; INTRODUCTION; Part I DISCERNMENT OF SPIRITS AND POSSESSION; Part II CONTACTS WITH THE OTHER WORLD; Part III DIVINATION, SHAMANISM; LIST OF CONTRIBUTORS; INDEX.
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Witchcraft -- Europe -- History -- Congresses; Demonology -- Europe -- History -- Congresses; Folklore -- Europe -- History -- Congresses; Sorcellerie -- Europe -- Histoire -- Congrès.; Démonologie -- Europe -- Histoire -- Congrès.; Folklore -- Europe -- Histoire -- Congrès.; BODY, MIND & SPIRIT -- Occultism; Demonology; Folklore; Witchcraft; Europe; Anthropology, Demonology, Folklore, Religion, Witchcraft; Conference papers and proceedings; History